Influence of the molecular-oriented structure of ionic liquids on the crystallinity of aluminum hydroxide prepared by a sol–gel process in ionic liquids. Issue 28 (28th July 2015) - Kinoshita, K.; Yanagimoto, H.; Suzuki, T.; Minami, H.
<x xml:space="preserve">Abstract</x> The influence of the structure of ionic liquids on the crystallinity of aluminum hydroxide (Al(OH)3) prepared by a sol–gel process with aluminum isopropoxide (Al(OPri)3) in imidazolium-based ionic liquids was investigated.